Accessibility and Referential Choice: Personal Pronouns and D-pronouns in Written German - Yvonne Portele; Markus Bader (Discours)
We present a corpus study and a production experiment that investigated the choice between two types of pronouns in written German – personal pronouns and so-called d-pronouns, which have properties of both personal and demonstrative pronouns. The existing research concerned with these pronouns has focused on language comprehension, in particular with regard to interpretative preferences in the case of referential ambiguity. In contrast to language comprehension, a choice between the two pronominal forms has to be made during language production whether there is an ambiguity or not. The corpus data show that the choice between p(ersonal) pronoun and d-pronoun depends on several factors that have been claimed to determine a referent’s accessibility (Ariel, 1990), in particular givenness and syntactic prominence (syntactic function and clausal position). The corpus study is supplemented by a production experiment that required participants to continue a short text passage with a sentence starting with either a p-pronoun or a d-pronoun. The results of the experiment strengthen the conclusion that several factors determine accessibility which in turn governs pronoun choice. We finally discuss several factors besides accessibility that affect the choice of either a p- or a d-pronoun.